Ответ:
х - любое число.
Пошаговое объяснение:
4х + 6 = 2( 2х + 3 )
4х + 6 = 4х + 6
4х - 4х = 6 - 6
0 = 0
.......................
проверим:
пусть х = 0
4 · 0 + 6 = 2 · ( 2 · 0 + 3 )
0 + 6 = 2 · ( 0 + 3 )
6 = 6
........
х = 100
4 · 100 + 6 = 2 · ( 2 · 100 + 3 )
400 + 6 = 2 · 200 + 6
406 = 406
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
х - любое число.
Пошаговое объяснение:
4х + 6 = 2( 2х + 3 )
4х + 6 = 4х + 6
4х - 4х = 6 - 6
0 = 0
х - любое число.
.......................
проверим:
пусть х = 0
4 · 0 + 6 = 2 · ( 2 · 0 + 3 )
0 + 6 = 2 · ( 0 + 3 )
6 = 6
........
х = 100
4 · 100 + 6 = 2 · ( 2 · 100 + 3 )
400 + 6 = 2 · 200 + 6
406 = 406